Massive star cluster formation under the microscope at z = 6. Issue 3 (6th December 2018) - Vanzella, E; Calura, F; Meneghetti, M; Castellano, M; Caminha, G B; Mercurio, A; Cupani, G; Rosati, P; Grillo, C; Gilli, R; Mignoli, M; Fiorentino, G; et al.
Abstract: We report on a superdense star-forming region with an effective radius ( R e ) smaller than 13 pc identified at z = 6.143 and showing a star formation rate density ΣSFR ∼ 1000 M⊙ yr −1 kpc −2 (or conservatively >300 M⊙ yr −1 kpc −2 ). Such a dense region is detected with S/N ≳ 40 hosted by a dwarf extending over 440 pc, dubbed D1. D1 is magnified by a factor 17.4(±5.0) behind the Hubble Frontier Field galaxy cluster MACS J0416 and elongated tangentially by a factor 13.2 ± 4.0 (including the systematic errors). The lens model accurately reproduces the positions of the confirmed multiple images with a rms of 0.35 arcsec. D1 is part of an interacting star-forming complex extending over 800 pc. The SED-fitting, the very blue ultraviolet slope (β ≃ −2.5, F λ ∼ λ β ), and the prominent Lyα emission of the stellar complex imply that very young (<10−100 Myr), moderately dust-attenuated ( E ( B − V ) < 0.15) stellar populations are present and organized in dense subcomponents. We argue that D1 (with a stellar mass of 2 × 10 7 M⊙ ) might contain a young massive star cluster of M ≲ 10 6 M⊙ and M UV ≃ −15.6 (or m UV = 31.1), confined within a region of 13 pc, and not dissimilar from some local super star clusters (SSCs). The ultraviolet appearance of D1 is also consistent with a simulated local dwarf hosting an SSC placed at z = 6 and lensed back to the observer. This compact system fits into some popular globular cluster formation scenarios. We show that future high spatial resolution imaging (e.g. E-ELT/MAORY-MICADO and VLT/MAVIS) will allow us to spatially resolve light profiles of 2–8 pc.